Life table for the female population of the county of Ribeirão Preto (State of S. Paulo, Brazil), 1973 - Carvalheiro, Clarisse D. G. (Revista de Saúde Pública, 1977)
The life table for the female population of the county of Ribeirão Preto (State of S. Paulo, Brazil), in the mid-year 1973, was constructed. The curve of survivors at successive ages and expectation of life at birth were compared with the values obtained by Duarte & Milanesi (1958) for 1950, for the same county. Expectation of life at birth, 65,3 years, was compared also with the values obtained for different regions of the State of S. Paulo in 1967, female population of the State of Rio Grande do Norte (40,0 years), of the State of Rio Grande do Sul (62,5 years) and Brazil as a whole (55,6 years) in 1970.